Analisis Implementasi ISAK 35 Pada YPI Ulil Albab Ar-rohman Kediri - Larasati, Putri; Nurdiwaty, Diah; Kurniawan, Andy (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2023)
This research is motivated by the problem of quality education that is not evenly distributed in urban and rural areas. School is an institution that can realize quality education. Yayasan Pendidikan is one of the legal entities that can help realize quality education that is evenly distributed in each region. In its operations, the Foundation obtains resources from givers who do not expect a return on the funds that have been donated. Therefore, the Foundation needs to make reliable and relevant financial statements to account for the funds that have been received in accordance with applicable Financial Accounting Standards. The location of this research is located at the Ulil Albab Ar-rohman Islamic Education Foundation located on Jl. Patimura No. 37, Sambi Village, Ringinrejo District, Kediri Regency, East Java Province. This study aims to determine the application of ISAK 35 in the Financial Statements of YPI Ulil Albab Ar-rohman Kediri. The method used in this research is a qualitative case study where in this case the researcher goes directly into the field to find out directly how the application of ISAK 35 in the Foundation's financial statements. The data collection technique used is a technique according to Miles and Huberman. Test the validity of findings using observation extension and data triangulation. The results of the study stated that YPI Ulil Albab Ar-rohman Kediri has not applied ISAK 35 at all in the presentation of the Foundation's financial statements because the constraints of incoming information are still very minimal.